KAJIAN KUALITAS PRODUK DAN VARIASI PRODUK TERHADAP LOYALITAS PELANGGAN BRAND OH MY GLAM - Anggit Dyah Kusumastuti; Rina Yuliastuti; Marshela Nur Rahma Zallyanti (Politeknik Negeri Ambon, 2026)
Introduction: The local cosmetic industry in Indonesia has experienced rapid growth, resulting in increasingly intense competition among cosmetic brands. OMG (Oh My Glam) is one of the local cosmetic brands that has attracted consumer attention through affordable prices and diverse product variations. In this competitive market, customer loyalty becomes an important factor in maintaining business sustainability. This study aims to analyze the influence of product quality and product variation on customer loyalty toward the OMG brand.Methods: This study applied a Systematic Literature Review (SLR) approach. Data were collected from relevant national journal articles published between 2021 and 2026 through Google Scholar. The selected literature was analyzed descriptively by identifying, comparing, and synthesizing findings related to product quality, product variation, and customer loyalty in the cosmetic industry.Results: The results indicate that product quality has a positive influence on customer loyalty, particularly in terms of product durability, ingredient safety, and suitability to consumer needs. Product variation also contributes positively to customer loyalty because it provides more choices that align with consumer preferences and beauty trends. In addition, the combination of product quality and product variation is considered effective in increasing repurchase intention, reducing switching behavior, and strengthening consumer trust in the OMG brand.Conclusion and suggestion: Product quality and product variation are important factors in building customer loyalty toward the OMG brand. Therefore, cosmetic companies, especially OMG, are encouraged to maintain product quality consistency and continuously develop product variations that are relevant to consumer needs and market trends in order to strengthen long-term customer loyalty. Keywords: Customer Loyalty; Literature Review; OMG; Product Quality; Product Variation;